Doppler flowmetry of feto-maternal circulation: III --Absent and reverse diastolic flow in the umbilical artery. - Graça, L M (1991)
Twelve cases of extreme umbilical blood flow impairement (8 cases with loss of end-diastolic blood flow and 4 cases with reversed flow) found among 658 pregnancies studied by continuous Doppler between April 1st 1989 and March 31st 1990, are reported. The findings were associated to intra-uterine growth retardation (92%), maternal hypertensive disease (50%) and perinatal death (33%); fetal Trisomy 21 was the sole problem in one of the cases with absent end-diastolic frequencies. Our results are discussed and compared to similar data reported recently. Clinical management is proposed, according to umbilical blood flow patterns, length of gestation and underlying clinical situations.